The Effect of an Educational Intervention Programme on Allied Health Students Knowledge, Attitude, and Practice Regarding Cardiopulmonary Resuscitation - Falastine Hamdan; Mohammad Etoom; Rafi Alnjadat; Eshraq Momani; Salwa Abu-ALrub (Jordan University of Science and Technology, 2024)
The Effect of an Educational Intervention Programme on Allied Health Students Knowledge, Attitude, and Practice Regarding Cardiopulmonary Resuscitation  What does this paper add? Interventional studies in Jordan regarding Cardiopulmonary Resuscitation (CPR) knowledge, attitude and practice in allied heath students are limited. Therefore, to provide pertinent information on this crucial topic for a rising country, such as Jordan. Emphasize learning CPR must be incorporated with skills, including the cooperation and proper communication between all health team members. Because of that, it is worth considering teaching CPR skills in all groups of health members at level of students, whom are the future encounter professionals. Falastine Hamdan: PhD, MSN, RN. Al-Balqa Applied University, Irbid University College, Salt, Jordan. falsteen.hamdan@bau.edu.jo. Mohammad Etoom: MSN, RN. Al-Balqa Applied University, Irbid University College, Salt, Jordan. Email: Maetoom@bau.edu.jo. Rafi Alnjadat: PhD, MSN, RN. Al-Balqa Applied University, Irbid University College, Salt, Jordan. Email: rafi.alnjadat@bau.edu.jo. Eshraq Momani: MSN, RN. Al-Balqa Applied University, Irbid University College, Salt, Jordan. Email: esshraq.momani@bau.edu.jo. Salwa Abu-ALrub: MSN, RN. Al-Balqa Applied University, Irbid University College, Salt, Jordan. Email: salwa.abual@bau.edu.jo. Correspondence author: Falastine Hamdan. Email: Falsteen.hamdan@bau.edu.jo.